Ensaio em laboratório da biorremediação da água eutrofizada da lagoa da Salina (Morada Nova - CE) com a branchoneta (Dendrocephalus brasiliensis Pesta, 1921) - Oliveira, Francisco Rafael de Araújo (2022)
The pollution of water resources is one of the main environmental problems that human actions can cause. This situation causes an increase in the concentration of nutrients in water, accelerating the process of eutrophication, making rivers, lakes and reservoirs unsuitable for better uses. Thus, the objective of this study was to improve the water quality of Salina lagoon (Morada Nova - CE), in a laboratory experiment through bioremediation, using the microcrustacean filter branchoneta, as well as to evaluate its efficiency in improving the chlorophyll a and total phosphorus parameters that compose the trophic state index (TSI). The experimental design is based on a 5x2x3 factorial analysis of variance (ANOVA), with two replicates in each cell. For 24 hours, adult branchonets were used in the lagoon water in 60 experimental units for a three-factor experiment: density of branchonets, at 5 levels: 0 (control), 25, 50, 75 and 100 branchonets per liter; dilution of lagoon water with drinking mineral water at two levels: concentration of water originally collected in the lagoon in natura and diluted to 50%; and the third factor, time for the three stages of the experiment, evaluated after 8h, 16h and 24h. At the end of the experiment the water samples were evaluated and with the chlorophyll a and total phosphorus data, the TSI was calculated. The classification of the Salina Lagoon, according to the CONAMA Resolution 357/2005, has an indication of Freshwater - Class IV, which can be exploited for navigation and landscape harmony, but other parameters should be evaluated for final classification. During the 24 hours of the tests, the branchonets did not present significant mortality, with a high survival rate measured at 94.75%. It was verified that the water quality of the Salina lagoon is not influenced by treatment with the branchoneta filter-feeding microcrustacean, where it was observed that according to the density of animals and the water concentration level, the quality of the trophic state does not improve significantly, although, there was an improvement in the trophic classification.